Application of Light Guide Plate and Light Emitting Diode for Plant Illumination by Using Drilling Holes as The Light Scatter - Prajuabwan, Pakorn (KKU Science Journal, 2026)
Circular shape acrylic Light Guide Plate (LGP) attached with strip Light Emitting Diode (LED) at circumference as artificial lighting for plant illumination is fabricated. LGP is an acrylic panel typically made from pure Polymethyl methacrylate (PPMA) resin which is extremely transparent, highly weather resistance and easily purchased. On the top or the bottom of the panel, a matrix of lines can be etched, called V-Cutting, dots can be printed, a combination of both, or particulates are added into the panel itself. The purpose of all methods is to direct light out the front of the panel. Dot printing is a matrix of fine dots which is printed onto the LGP using diffusive ink. These dots help scatter the light emitted from the light source. Dot printing is a quicker and cheaper process than V-cutting however, not always the desired method. The major disadvantage of dot printing is that ink is less effective at refracting light and therefore not as bright. Many backlighting applications require a very bright light that dot printing cannot accomplish. A simple technique to scatter the light from the light source through LGP by making a matrix of drilling holes as the concave lens all over LGP panel is proposed. This technique with LGP can be used to mix red and blue strip LED light source with appropriate ratio between red and blue colour to be artificial lighting for plant illumination. In general, artificial LED lighting for plant illumination, the ratio between red and blue color is always fixed by the manufacturer of LED panel. The user cannot adjust the fixed red and blue ratio. With LGP technique, the user can design the ratio of red and blue color LED by selecting the number of red LED and blue LED to attach at the circumference of LGP. In this experiment, the light intensity of various ratios of mixed red color and blue color are measured with light spectrum instruments compared to the light intensity of unmixed red color and unmixed blue color. With this artificial lighting for plant illumination, wheatgrass sprouts grown result and their chlorophyll extraction results are examined to confirm the possibility in using this technique.